Ties between reading faces, bodies, eyes, and autistic traits - Pavlova, Marina A.; Romagnano, Valentina; Kubon, Julian; Isernia, Sara; Fallgatter, Andreas J.; Sokolov, Alexander N. (Frontiers in Neuroscience, 2022)
While reading covered with masks faces during COVID-19 pandemic, for efficient social interaction, we need to combine information from different sources such as eyes (without faces hidden by masks) and bodies. This may be challenging for individuals with neuropsychiatric conditions, in particular, autism spectrum disorders. Here we examined whether reading of dynamic faces, bodies and eyes are tied in a gender-specific way, and how these capabilities are related to autistic traits expression. Females and males accomplished a task with point-light faces expressing happiness and angriness along with a task with point-light body motion portraying angry and neutral locomotion. They had to infer emotional content of displays. In addition, participants were administered the Reading the Mind in the Eyes Test, modified and Autism Spectrum Quotient questionnaire. The findings show that only in females, inferring emotions from dynamic bodies and faces are firmly linked, whereas in males, reading in the eyes is knotted with face reading. Strikingly, in neurotypical males only, accuracy of face, body and eyes reading was negatively tied with autistic traits. The outcome points to gender-specific modes in social cognition: females rely upon merely dynamic cues while reading faces and bodies, whereas males most likely trust configural information. The findings are of value for examination of face and body language reading in neuropsychiatric conditions, in particular, autism, most of which are gender/sex specific. This work suggests that if male individuals with autistic traits experience difficulties in reading covered with masks faces, these deficits may be unlikely compensated by reading (even dynamic) bodies and faces. In contrast, in females, reading covered faces as well as reading language of dynamic bodies and faces are not compulsory connected to autistic traits preventing them of paying high costs for nonadaptive social interaction.